Decreasing costs of renewables: Implications for Indonesia's climate targets - Johannes Eckstein; Jose Antonio Ordonez; Jakob Wachsmuth (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
The unconditional target of Indonesia's NDC foresees a reduction of GHG emissions of 29% relative to a Business-as-Usual (BAU) scenario, to reach 2034 MtCO2eq in 2030. It further specifies that the energy sector shall take a share of 37.6% of this mitigation effort to reduce emissions by 18.8% relative to BAU, reaching 1355 MtCO2eq emissions in 2030. This study analyses how falling cost projections of renewable energy technologies (solar PV and wind energy) could inform energy sector and climate change mitigation plans of Indonesia.We show that cost projections valid for Indonesia for renewable energies have dramatically fallen over the past years. Costs projected for 2030 a couple of years ago are well undercut by more recent projections for 2030. Recent cost projections for 2030 for wind energy are 31% lower than projections dating from 2015, solar PV cost projections have fallen by 49% on average. If falling costs for renewables are considered, the renewable capacities given in RUEN (the National Energy Master Plan) could be revised at constant investments. The overall renewable energy capacity given in RUEN for 2030 could be increased from 70 GW to 85 GW. Solar PV would become the dominant source of renewable energy, wind energy would slightly surpass geothermal power generation. This increase in renewable capacities could inform the revision of Indonesia's NDC. If falling cost projections of renewables are considered, the unconditional target could be reduced from 2034 MtCO2eq to 2005 MtCO2eq at constant costs. This corresponds an increase from 29% to 30.1% reduction and presents a 9.1% increase in the ambition of the energy sector.
urn:nbn:de:0011-n-6156249
Keywords: 330